Characteristics of dysphagia among different lesion sites of stroke: A retrospective study - Qiao, Jia; Wu, Zhi-min; Ye, Qiu-ping; Dai, Meng; Dai, Yong; He, Zi-tong; Dou, Zu-lin (Frontiers in Neuroscience, 2022)
Objective This study aims to compare the characteristics of dysphagia among different lesion sites and explore the possible risk factors that are relevant to penetration and aspiration after stroke. Materials and methods Data on patients with post-stroke dysphagia were collected. Major measures of the videofluoroscopic swallowing study included pharyngeal transit duration (PTD), pharyngeal response duration (PRD), soft palate elevation duration (SED), stage transition duration (STD), hyoid bone anterior-horizontal displacement (HAD), hyoid bone superior-horizontal displacement (HSD), upper esophageal sphincter opening (UESO), Pharyngeal Residual Grade (PRG), and Penetration Aspiration Scale (PAS). Included patients were divided into supratentorial (deep or lobar intracerebral) and infratentorial stroke groups. The Kruskal–Wallis test, Spearman’s correlation analysis, and multivariate logistic regression analyses were used to test the difference and the correlation between those measures. Time-to-event endpoints (oral feeding) were analyzed by the Kaplan–Meier method. Results A total of 75 patients were included in this study. Significant differences were demonstrated in PTD, PRD, SED, STD, HAD, HSD, UESO, PAS, and PRG between supratentorial and infratentorial stroke groups (p < 0.05). The PRG score of the lobar intracerebral subgroup was significantly higher (p < 0.05) than that of the deep intracerebral and lobar + deep intracerebral stroke subgroups, while HSD was significantly shorter (p < 0.01). Spearman’s correlation analysis revealed that PAS was related to PTD, PRG, HAD, and UESO (p < 0.05). Multivariate logistic regression analysis demonstrated that HAD and PRG may be risk factors for penetration and aspiration (p < 0.05). Kaplan–Meier survival plot showed that there was a significant difference in time to oral feeding between supratentorial and infratentorial stroke groups (p < 0.01). Conclusion Infratentorial stroke may lead to worse swallowing function as compared with supratentorial stroke, and lobar intracerebral stroke may be worse than deep intracerebral stroke. Suitable preventive measures may be considered for patients with higher PRG scores and shorter HSD to avoid penetration and aspiration.